33. CHARACTERISTICS OF HISTOPATHOLOGY, GRADE AND pTNM STAGE OF OPERATED LUNG ADENOCARCINOMA AT THE NATIONAL LUNG HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the histopathological characteristics, histological grade, and Ptnm staging of operated lung adenocarcinoma based on the guidelines of the WHO 2021 classification.Methods: Cross-sectional descriptive study on patients with operated lung adenocarcinoma (≥18 years old) admitted to the National Lung Hospital from January to December 2022. We collected data on clinical and histopathological characteristics, pTNM stage, histological grade are new points in the 2021 histopathological classification.Results: 186 patients with operated lung adenocarcinoma were collected and evaluated for target characteristics with a predominance in men (54.8%), smokers (58.1 %); age 60 or older (56.5%) with the largest number being in the 60-69 age group; Stage IB accounts for the highest rate. The most common histopathological type is invasive non-mucinous adenocarcinoma (97.8%), with the dominant acinar eubtype accounting for the highest proportion; histological grade III is the most common with a rate of 51.1%, predominantly in patients over 60 years old, smokers (p < 0.05), stages II, IIIA; The STAS pattern (tumor spread in the air space) appears in 25.8% of cases, accounting for a higher proportion under the dominant micropapillary type and histological grade III (p
Keywords: Lung adenocarcinoma, EGFR mutation, histopathological characteristics, early stage lung cancer.